A three-dimensional in vitro model of the peripheral nervous system - Park, Sunghee Estelle; Ahn, Jinchul; Jeong, Hyo-Eun; Youn, Inchan; Huh, Dongeun; Chung, Seok (NATURE RESEARCH, 2021)
Recent advances in three-dimensional (3D) cell culture models developed on organ-on-a-chip or microfluidic devices have shown their capability to recapitulate the in vivo microenvironment as well as their potential as tools in biomedical research. Here, we present an in vitro model of the peripheral nervous system (PNS) by establishing a coculture model of motor neurons (MNs) and Schwann cells (SCs) in a 3D environment in a microengineered extracellular matrix hydrogel scaffold. The collagen scaffold placed at the center of the microdevice provided a 3D cellular microenvironment where the axons of MNs were allowed to actively interact with SCs during their growth and maturation. By treating the MN-SC coculture model with ascorbic acid, we were able to model the myelination process in the PNS, which was evidenced by the increased expression of myelin markers in SCs. Moreover, we show that this can be reversed by treating myelinated nerve fibers with glial growth factor (neuregulin-1 isoform) to potentially block the formation of the myelin sheath and induce demyelination. Our 3D cell culture model may be used to achieve active control of the myelinating and demyelinating processes in the PNS and thus may offer new opportunities to study pathophysiological processes involved in motor neuron diseases by in vitro modeling.
Keywords: SCHWANN-CELLS; MYELINATED AXONS; CULTURE; NODES; DIFFERENTIATION; MOTONEURONS; GLIOMEDIN; MIGRATION